Interdictions in Lithuanian Paremias: Links with Mythological Beliefs - Džekčioriūtė, Vita (Tautosakos darbai, 2026)
The article focuses on two types of conversational genre: proverbs and beliefs. The study aims to highlight three aspects of Lithuanian paremias: the establishment of certain social norms through interdiction, the expression of a mythological mindset through imagery, and interaction with another genre of short folklore, namely, belief. The article analyses proverbs related to the mythological mindset, grouping them into eight different themes. The study also discusses aspects of the expression of interdictive proverbs. Reviewing the entire collection of Lithuanian mythological paremias with interdictions shows that some belief and proverb texts are identical or very similar in form. In such cases, attribution to the particular genre of folklore depends on the context in which these texts are used.
Keywords: conversational folklore; beliefs; mythological mindset; paremiology; social norms; interaction of genres